2022
DOI: 10.1007/s12274-022-4637-3
|View full text |Cite
|
Sign up to set email alerts
|

Structure inversion asymmetry enhanced electronic structure and electrical transport in 2D A3SnO (A = Ca, Sr, and Ba) anti-perovskite monolayers

Abstract: Anti-perovskites A3SnO (A = Ca, Sr, and Ba) are an important class of materials due to the emergence of Dirac cones and tiny mass gaps in their band structures originating from an intricate interplay of crystal symmetry, spin-orbit coupling, and band overlap. This provides an exciting playground for modulating their electronic properties in the two-dimensional (2D) limit. Herein, we employ first-principles density functional theory (DFT) calculations by combining dispersion-corrected SCAN + rVV10 and mBJ funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 100 publications
0
11
0
Order By: Relevance
“…[10][11][12][13] The atomic structure of 2D monolayers can exist in many different symmetry forms at the ground state, such as 1T, 2H, and 3R. 14,15 Many 2D materials have a stable structure in the 2H phase (hexagonal structure) and this is also the most investigated structure according to our observations. However, RuS 2 (and also RuSe 2 ) is one of those unusual materials.…”
Section: Introductionmentioning
confidence: 82%
“…[10][11][12][13] The atomic structure of 2D monolayers can exist in many different symmetry forms at the ground state, such as 1T, 2H, and 3R. 14,15 Many 2D materials have a stable structure in the 2H phase (hexagonal structure) and this is also the most investigated structure according to our observations. However, RuS 2 (and also RuSe 2 ) is one of those unusual materials.…”
Section: Introductionmentioning
confidence: 82%
“…, LMBJ, 31 TASK, 32 and mTASK 33 meta-GGA functionals) which may have potential applications in the future for a better manifestation of 2D semiconducting and semi-metallic systems. 34,35…”
Section: Computational Detailsmentioning
confidence: 99%
“…It is to be noted that some new exchangecorrelation potentials proposed in the recent literature (e.g., LMBJ, 31 TASK, 32 and mTASK 33 meta-GGA functionals) which may have potential applications in the future for a better manifestation of 2D semiconducting and semi-metallic systems. 34,35 The top and side views of a monolayer MoSi 2 N 4 , along with its band structure are shown in Fig. 1.…”
Section: Computational Detailsmentioning
confidence: 99%
“…On the other hand, introducing inversion asymmetry in these inverse perovskites enhances their experimentally observed thermoelectric properties. [2,13] Among the potential 3D A 3 BO Dirac systems capable of exhibiting topological surface states, Sr 3 PbO (SPO) inverse perovskite crystallizes in the perfect cubic phase with space group # 221 (Pm-3 m) and a lattice parameter of 5.15 Å that does not undergo any structural phase transitions for a wide range of temperatures. [14,15] While the strontium and oxygen ions in SPO adopt their usual þ2 and À2 valence states, respectively, an unusual À4 oxidation state for the Pb atom is in general responsible for giving this material its nontrivial electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, theoretical studies on bulk systems have also strengthened the prospect of realizing topologically nontrivial electronic structure in thin solid films of A 3 BO inverse perovskites where band inversions might be controlled with layer thickness. [13,18] On the other hand, DFT calculations have also highlighted that sandwiching SPO layers in LaCrO 3 perovskite can be useful for realizing exotic electron behavior such as quantum anomalous Hall effect. [20] Recent experimental studies have shown that the epitaxially grown thin films of SPO on LaAlO 3 substrate exhibit a metallic character with p-type carrier density of around 10 20 cm À3 .…”
Section: Introductionmentioning
confidence: 99%